(untitled) (Academia Journal of Medicine, 2024)
Gilbert syndrome is a rare benign autosomal genetic disorder characterized by reduced activity of glucuronyl transferase, leading to decreased clearance of bilirubin and occasional mild jaundice in the absence of hepatic injury or hemolysis. Diagnosis involves clinical and laboratory investigations as part of differential diagnosis, with genetic analysis providing additional confirmation. Oral manifestations of Gilbert syndrome exist but often go unnoticed. Drugs metabolized by this enzyme need to be considered along with stress management in patients undergoing surgical procedures. This case report of a 24- year-old male diagnosed with a radicular cyst in the maxillary anterior teeth region, who incidentally exhibited Gilbert syndrome, also highlights perioperative management considerations for such patients.